أهمية عقيدة ختم النبوة فى ضوء القرآن والسنة: The Importance of the Doctrine of the Finality of Prophethood in Light of the Qur’an and Sunnah (Al-Aasar, 2025)
The doctrine of Khatm-e-Nubuwwat (Finality of Prophethood) holds a central position in Islamic theology, affirming that Prophet Muhammad (peace be upon him) is the last and final messenger of Allah. This belief is deeply rooted in the Qur'an and Sunnah, with multiple verses and authentic Hadiths explicitly stating that no prophet shall come after him. The Qur'an, particularly in Surah Al-Ahzab (33:40), declares him as the "Seal of the Prophets," reinforcing the completeness and perfection of the divine message. The Sunnah further clarifies this concept through numerous narrations emphasizing the finality of his prophethood.This paper examines the significance of Khatm-e-Nubuwwat in light of the Qur'an and Hadith, exploring its implications for Islamic faith, religious integrity, and societal stability. It also highlights the historical consensus among scholars and the necessity of upholding this belief to preserve the authenticity of Islam. Any deviation from this fundamental doctrine poses a serious challenge to Islamic theology and unity. By analyzing scriptural evidence and scholarly interpretations, this study aims to reaffirm the critical role of Khatm-e-Nubuwwat in maintaining the purity of Islamic teachings.